Antibiotic resistance rates in Cutibacterium acnes isolated from patients with acne vulgaris: a systematic review and meta-analysis - Zhu, Chunxiao; Wei, Baozhen; Li, Yang; Wang, Changyuan (Frontiers in Microbiology, 2025)
BackgroundCutibacterium acnes (C. acnes) is closely related to the pathogenesis of acne, and studies related to the antibiotic resistance rates of C. acnes have been reported worldwide; however, relevant systematic reviews and meta-analyses are still lacking. The aim of this study was to systematically evaluate the resistance in C. acnes to relevant antibiotics, that this information may be used to provide a rational basis for the antibiotic treatment of acne.MethodsRelevant studies in PubMed, the Cochrane Library, EMBASE, Web of Science, China National Knowledge Infrastructure (CNKI) and Wanfang Data were systematically searched from January 1, 2005, to April 1, 2025, and the resistance rates of C. acnes isolates to quinolones, macrolides, tetracyclines, and other relevant antibiotics were collected. The combined resistance rate was calculated via the R language program package 4.3.2, with subgroup analyses based on different years, continents, countries, provinces in China and different drug susceptibility testing methods.ResultsA total of 8,846 studies were systematically retrieved and 23 studies were included, corresponding to 2,046 isolates of C. acnes, which have shown antibiotic resistance rates ranging from high to low: 48.17% (95% CI: 41.16–55.24%) for roxithromycin, 45.64% (95% CI: 20.49–73.22%) for clarithromycin, 43.33% (95% CI: 27.81–60.29%) for azithromycin, 29.20% (95% CI: 22.14–37.43%) for erythromycin, 22.38% (95% CI: 14.69–32.56%) for clindamycin, 5.93% (95% CI: 2.91–11.69%) for levofloxacin, 2.44% (95% CI: 0.99–5.89%) for doxycycline, 1.47% (95% CI: 0.00–85.72%) for trimethoprim-sulfamethoxazole (TMP–SMX), 1.31% (95% CI: 0.45–3.70%) for tetracycline, 0.28% (95% CI: 0.04–1.94%) for chloramphenicol, 0.22% (95% CI: 0.03–1.89%) for minocycline. Subgroup analysis revealed that, compared with those in other regions, the resistance rates to macrolides and clindamycin were higher in China. In addition, the levofloxacin, erythromycin, and clindamycin resistance rates were progressively increasing over time.ConclusionIn certain regions, the relatively high antibiotic resistance rates (e.g., 77% (95% CI: 62–87%) for clarithromycin in China) in C. acnes isolates may be attributed to the overuse of antibiotics in acne treatment. The resistance rates in C. acnes to tetracyclines, such as 2.44% (95% CI: 0.99–5.89%) for doxycycline, remain relatively low, which allows tetracyclines to continue serving as first-line antibiotics for acne treatment. In addition, the resistance rates to levofloxacin, erythromycin, and clindamycin markedly increased over time (p < 0.05). This emphasizes the significance of rational use of the antibiotics in acne treatment.